Optimal Bracing Type of Reinforced Concrete Buildings with Soil-Structure Interaction Taken into Consideration - Yassine Razzouk; Mohamed Ahatri; Khadija Baba; Ahlam El Majid (Civil Engineering Journal, 2023)
This study aims to investigate the impact of soil-structure interaction (SSI) on the seismic behavior of reinforced concrete buildings. An advanced numerical model for SSI was developed and verified using ABAQUS software. The seismic response of a 12-story building on four types of soil (rock, dense soil, stiff soil, and soft soil) was examined using a Normalized Response Spectra based on the Moroccan paraseismic regulation RPS 2011. The global lateral displacement, inter-story drift, and period were compared for two types of bracing (column and shear wall). The results show that SSI has a significant impact on the seismic behavior of buildings, and the seismic responses of soil-structure systems with column and shear wall bracing are quite different. The research contributions of this paper include developing an advanced numerical model for SSI, examining the impact of SSI on the choice of bracing for reinforced concrete buildings, and providing guidance on the most reliable bracing method for structures of various heights and soil types. The study's findings have important implications for seismic design and can help improve the safety and reliability of buildings in earthquake-prone regions. The study also highlights the importance of considering SSI in seismic design and the need for guidelines that describe the bracing systems to be used based on the structure's height and type of soil. Doi: 10.28991/CEJ-2023-09-06-06 Full Text: PDF